Penerapan Model Penilaian Autentik Terhadap Pembelajaran Menulis Cerpen - ., Serlina; Baan, Anastasia; Fitriana, Irna (CV. ITTC INDONESIA, 2024)
The aim of this research is to describe the teacher's planning in carrying out authentic assessment applied to Indonesian language subjects and to describe the application of the authentic assessment model to the short story writing learning of Class IX students of SMP Negeri 1 Pana. The research was conducted as a qualitative type of research and used a case study approach. Data collection procedures were carried out using observation, interviews and documentation methods. Data analysis includes data collection, data reduction, data presentation and data verification. The results of the research are that (1) The implementation of the 2013 Curriculum at SMP Negeri 1 Pana has been carried out even though the implementation was carried out in a gradual manner and in this year's learning the 2013 curriculum has been implemented in all classes. (2) The implementation of authentic assessment in Indonesian language learning at SMP Negeri 1 Pana has been carried out in accordance with the provisions of the 2013 curriculum. (3) Preparation for authentic assessment carried out by Indonesian language subject teachers on knowledge competency. (4) Implementation of authentic assessment in Indonesian language learning on knowledge competencies using written test techniques, oral tests and assignments.